Interactions between metabolism of trace metals and xenobiotic agonists of the Ah receptor in the Antarctic fish Trematomus bernacchii: environmental perspectives - REGOLI, Francesco; BENEDETTI, MAURA; GORBI, STEFANIA; FATTORINI, DANIELE; NIGRO M; PRETTI C; GERVASI P. G (Environmental Toxicology and Chemistry, 2005)
Although Antarctica is a pristine environment, organisms are challenged with contaminants either released locally or transported from industrialized regions through atmospheric circulation and marine food webs. Organisms from Terra Nova Bay also are exposed to a natural enrichment of cadmium, but to our knowledge, whether such environmental conditions influence biological responses to anthropogenic pollutants has never been considered. In the present study, the Antarctic rock cod (Trematomus bernacchii) was exposed to model chemicals, including polycyclic aromatic hydrocarbons (benzo[a]pyrene), persistent organic pollutants (2,3,7,8-tetrachlorodibenzo-p-dioxin [TCDD]), cadmium, and a combination of cadmium and TCDD. Analyzed parameters included chemical bioaccumulation, activity, and levels of biotransformation enzymes (cytochrome P4501A); metallothioneins and the efficiency of the antioxidant system measured as individual defenses (catalase, glutathione, glutathione reductase, glutathione S-transferases, and glutathione peroxidases); and total scavenging capacity toward peroxyl and hydroxyl radicals. Reciprocal interactions between metabolism of inorganic and organic pollutants were demonstrated. Dioxin enhanced the accumulation of cadmium, probably stored within proliferating endoplasmic reticulum, and cadmium suppressed the inducibility of cytochrome P4501A, allowing us to hypothesize a posttranscriptional mechanism as the depletion of heme group availability. Clear evidence of oxidative perturbation was provided by the inhibition of antioxidants and enhanced sensitivity to oxyradical toxicity in fish exposed to organic chemicals. Exposure to cadmium revealed counteracting responses of glutathione metabolism; however, these responses did not prevent a certain loss of antioxidant capacity toward peroxyl radicals. The pattern of antioxidant responses exhibited by fish coexposed to cadmium and TCDD was more similar to that observed for cadmium than to that observed for TCDD. The overall results suggest that ...